Iodisasi Bakso dan Nilai Kesukaan - Henky Isnawan Hendritomo (JURNAL ILMU KEFARMASIAN INDONESIA, 2004)
The investigation of Iodized bakso and favorable value was carried out. The lodized bakso used iodine salts as follow KI, KIO,, and NaI each was added 200 ppm, and each treatment with three replicate. Sampling was difference as knead, raw bakso and cooked bakso. The result shows that are processing step very influential to decrease of iodine contain in bakso. The stability of KIO, during processing better than KI or Nal. Generally iodized bakso does not appear side effect to consumer, although in the texture of bakso. The consumer prefers iodized bakso. The iodized bakso with Nal most favorable than iodized bakso with KIOZ.